Synthesis, Characterization and Biological Evaluation of Ciprofloxacin-p-nitrobenzoylated and Its Transition Metal Analogues: Synthesis and Biological Evaluation - Rabbani, M. G.; Islam, M. R. (Journal of Scientific Research, 2019)
Six novel transition metal complexes of ciprofloxacin-p-nitro benzoyl derived from ciprofloxacin have been synthesized to find out their medicinal evaluation. It has been characterized by different techniques, i.e., UV-Vis, IR, NMR and mass spectrometry together with elemental analysis and molar conductivity. All the compounds were screened for their antimicrobial activities by the disc diffusion method. Cytotoxicity was also made against brine shrimp lethality assay. The antimicrobial activity of the analogues compared with the parent was evaluated against three Gram-positive, seven Gram-negative bacterial strains and three fungi. The synthesized compounds demonstrated a variety of antibacterial profiles among which most of the analogues showed a comparable or better activity compared to the ciprofloxacin. Moreover, unlike ciprofloxacin, most of the derivatives were also found to show antifungal activity. Interestingly, all the derivatives possessed an enhanced activity in comparison to the ciprofloxacin against Candida albicans. Regarding cytotoxicity, most of the derivatives showed to a greater degree cytotoxic agent compared to ciprofloxacin.